Active noise and vibration control : selected, peer reviewed papers from the 12th Conference on Active Noise and Vibration Control Methods (MARDiH'2015), June 8-11, 2015, Kraków, Poland (Diffusion and defect data. Solid state phenomena, 2016)
This book is a result of scientific meeting of people working on active noise and vibration control methods and problems. The control of noise and vibration has been always proved to be a difficult task and in many cases it is not feasible. For many years, passive, active and semi-active techniques have been considered and developed. Flexible isolation systems or structural damping, control of suspension parameter or generating active force are used for vibration and noise control. The most important technics of vibration mitigation are active methods so the book collects papers as a contribution to discussion. Noise Control, Vibration Control, Vibration Reduction, Nonlinear Systems, Optimal Control, Energy Harvesting, Shape Memory Alloy, Piezoelectric Mechatronics.